Analysis of Hydrogen Use in Gas Turbine Plants - V. A. Sednin; A. V. Sednin; A. A. Matsyavin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Improvement of the efficiency of modern power systems requires the development of storage technologies, optimization of operation modes, and increased flexibility. Currently, various technical solutions are used for electricity storage. The results of a literary review with an analysis of existing energy storage systems are presented, their advantages and disadvantages are considered. One of the promising solutions is the use of hydrogen as an energy storage medium. The creation of corresponding energy complexes makes it possible to obtain hydrogen by electrolysis of water, and then use it to cover peak loads. Various schemes with hydrogen-fired gas turbines with a pressure up to 35 MPa and a temperature of 1500–1700 °C were considered. The new scheme of power plant with hydrogen-fired gas turbines was synthesized, which includes a power block, hydrogen generation blocks and hydrogen and oxygen preparation unit for burning. An atmospheric electrolyzer was considered as a hydrogen and oxygen generator. For the proposed scheme, parametric optimization was performed, where the storage efficiency factor has been used as a criterion. The influence of inlet temperature in the combustion chamber, the compression rate of hydrogen and oxygen, as well as the specific energy costs of the electrolyzer were analyzed. The results of the numerical experiment were approximated in the form of polynomial dependencies, and can be used in further research on the economic efficiency of proposed power plant.